(untitled) (Web of Teachers: Inderscience Research, 2026)
Medical terminology represents an essential component of professional language in both English and Uzbek. This article explores the etymological resources of medical terms in the English and Uzbek languages from a comparative perspective. The study aims to identify the principal sources of term formation, including Latin and Greek borrowings, native lexical units, and intermediary influences, as well as to examine their historical development and adaptation. The research is based on a comparative and etymological analysis of medical terms selected from authoritative dictionaries and professional medical texts. The findings indicate that English medical terminology is largely formed through direct borrowings from classical languages, whereas Uzbek medical terminology reflects a mixed system combining international terms, Russian-mediated borrowings, and native word-formation elements. The study reveals both universal and language-specific features in the etymological structure of medical terms and underlines the significance of etymology in understanding terminological meaning, ensuring translation accuracy, and supporting terminology standardization. The results may be useful for further research in medical linguistics, comparative terminology, and English for Specific Purposes.